Analysis of Mouse Brain Transcriptome After Experimental Duvenhage Virus Infection Shows Activation of Innate Immune Response and Pyroptotic Cell Death Pathway - Koraka, Penelope; Martina, Byron E. E.; van den Ham, Henk-Jan; Zaaraoui-Boutahar, Fatiha; van IJcken, Wilfred; Roose, Jouke; van Amerongen, Geert; Andeweg, Arno; Osterhaus, Albertus D. M. E. (Frontiers in Microbiology, 2018)
Rabies is an important neglected disease, characterized by invariably fatal encephalitis. Several studies focus on understanding the pathogenic mechanisms of the prototype lyssavirus rabies virus infection, and little is known about the pathogenesis of rabies caused by other lyssaviruses. We sought to characterize the host response to Duvenhage virus infection and compare it with responses observed during rabies virus infection by gene expression profiling of brains of mice with the respective infections. We found in both infections differentially expressed genes leading to increased expression of type I interferons, chemokines and proinflammatory cytokines. In addition several genes of the interferon signaling pathway are upregulated, indicating a strong antiviral response and activation of the negative feedback mechanism to limit type I interferon responses. Furthermore we provide evidence that in the absence of significant neuronal apoptotic death, cell death of neurons is mediated via the pyroptotic pathway in both infections. Taken together, we have identified several genes and/or pathways for both infections that could be used to explore novel approaches for intervention strategies against rabies.